HUBUNGAN FAKTOR LINGKUNGAN DAN PERILAKU MASYARAKAT DENGAN KEBERADAAN JENTIK NYAMUK PENULAR DEMAM BERDARAH DENGUE (DBD) DI WILAYAH KERJA PUSKESMAS KUTA UTARA - NUGRAHANINGSIH, MARDIYANI; ADIPUTRA, N; ARYANTA, I Wayan REDI (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2010)
Dengue Hemorrhagic Fever (DHF) disease represents one of the important public health problems in Indonesia and it often generates an extraordinary occurrence of vast number of deaths. The research aims to know environmental factors and public behaviors which have relationship to the existence of mosquitoes larvae in the work area of North Kuta Public Health Centre. The result of this research shows that the environmental factors which are related to the existence of mosquitoes larvae are air humidity (p=0.000), the existence of obstructive drainage (p=0.000) and the existence of containers (p=0.000). The public behaviors which are associated with the existence of mosquitoes larvae are attitude (p=0.001) and the actions of people (p=0.000). In conclusion, the environmental factors which are related to the existence of mosquitoes larvae are air humidity, the existence of obstructive drainage and the existence of containers. The public behaviors which are associated with the existence of mosquitoes larvae are attitude and the actions of people. It is suggested that the people should participate more in the prevention of DHF disease by removing the nests of mosquitoes, and the Public Health Departement should put more attention to the environmental factors which are associated with the existence of mosquitoes larvae.
Keywords: Environmental factors, public behaviors, the existence of mosquitoes larvae